Particularities of Subjective Element of the Crime in French Criminal Law - Tsikarishvili, Kakha (Journal of Law, 2017)
French criminal law is characterized by many particular features, which make it different not only from the common law systems but also other countries of continental Europe. The Mens Rea of the crime is also quite peculiar. In difference with Georgian criminal law, in French law, the motive and purpose of the crime are not deemed to be part of subjective element of corpus delicti, while dolus eventualis is not considered to be a form of intention; in crimes accompanied by secondary consequences, as well as in cases, where the principle offender acts beyond common intent, as well as in so called contraventions, elements of objective imputation may be present.